Seed discolouration of rice: Location of inoculum and influence on nutritional value - V.K. AGARWAL, I.P. SACHAN and (Indian Phytopathology, 2002)
The seedborne inoculum of Alternaria alternata (responsible for ash grey discolouration) and Helminthosporium oryzae (responsible for black discolouration, dark purple discolouration, dark brown spots and light to dark brown dot like spots) were foundin seed coat and endosperm of discoloured seeds whereas fungi, namely, Curvularia geniculata, C. lunata (responsible for eye shape spot), Fusarium equiseti, F. graminearum, F. rnoniliforme (responsible for light pink discolouration) and Sarocladium oryzae (responsible for light brown discolouration) were found in seed coat, endosperm and embryo of discoloured seeds. Fungi associated with ash grey discolouration (A. alternata), light brown discolouration, (S. oryaze), black discolouration (H. oryzae), dark purple discolouration (H. oryzae), dark brown spots (H. oryzae) and light to dark brown dot like spots (H. oryzae) resulted in decrease in starch content as compared to healthy seeds. The reduction in starch content was higher in the seeds having discolouration on both embryo plus endosperm region as compared to lower categories of discolourations. In seeds with black discolouration dark brown spots and dark purple discolouration, a higher amount of protein was detected as compared to healthy seeds.Whereas, in seeds with grey discolouration, a decrease in the protein content was noted.